2014
DOI: 10.1080/17564905.2014.929412
|View full text |Cite
|
Sign up to set email alerts
|

Rogue diva flows: Aoi Sola's reception in the Chinese media and mobile celebrity

Abstract: Theorizations of celebrity often contend with questions of the constructed nature of star persona. This is more so the case when discussing divas in Japan, as they are subject to a wide range of gender regimes that mould the ways in which their persona is produced and consumed. Contemporary forms of transnationalism in East Asia, however, have created media flows and fan bases that provide new opportunities for Japanese female celebrities to reconstruct their star personas, transcending their celebrity status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…And Google and its associated services, such as Youtube, withdrew from China in 2010 after disputes over censorship. The common practice of using VPNs to side-step oicial bans have been called 'crossing over the wall' (fanqiang), and they have enabled motivated fans of international pop culture, such as fans of the Japanese celebrity Aoi Sola (Coates 2014(Coates , 2017, to participate in Twitter and Facebook discussions. At the same time, censorship measures have ensured that, in practice, non-Chinese social media platforms that appear seemingly ubiquitous worldwide, are far less popular than their Chinese counterparts.…”
Section: The Alterity Of Digital Chinamentioning
confidence: 99%
“…And Google and its associated services, such as Youtube, withdrew from China in 2010 after disputes over censorship. The common practice of using VPNs to side-step oicial bans have been called 'crossing over the wall' (fanqiang), and they have enabled motivated fans of international pop culture, such as fans of the Japanese celebrity Aoi Sola (Coates 2014(Coates , 2017, to participate in Twitter and Facebook discussions. At the same time, censorship measures have ensured that, in practice, non-Chinese social media platforms that appear seemingly ubiquitous worldwide, are far less popular than their Chinese counterparts.…”
Section: The Alterity Of Digital Chinamentioning
confidence: 99%
“…The Japanese pornography industry is arguably the cornerstone of Asian pornography as a whole. Research by Wong and Yau (2015), Coates (2014), and Jacobs (2011), among others, has demonstrated that Japanese pornography remains dominant throughout the region, influencing not only sexual tastes but also the practice of amateur pornographic production in the region. As a number of articles in this special issue demonstrate, Japanese male porn stars have a particularly large impact on people's sexual aspirations in both Japan and throughout the larger East Asian region.…”
Section: Reflections On Researching Pornography Across Asia: Voices Fmentioning
confidence: 99%
“…Aoi Sola's transnational celebrity status is constituted by multiple highly mobile public personas that carefully negotiate different cultural milieus (Coates 2014). Born in 1983 in Tokyo, Sola originally became a minor celebrity in Japan in the early 2000s through her roles in pornographic and pink films, which are erotically charged and occasionally explicit avant-garde films.…”
mentioning
confidence: 99%